Analysis of the variables that influence the implementation of early warning systems for toxicological emergencies - Raúl José Martelo Gómez; Piedad Mary Martelo Gómez; Annherys Isabel Paz Marcano (International Journal of Medical Toxicology and Legal Medicine, 2024)
Early warning system alternatives for toxicological emergencies are vital for reducing environmental and public health risks. This exploratory study, using the MICMAC technique, defined and identified the most relevant variables guiding the implementation of early warning systems. After conducting an exhaustive bibliographic review and interviewing experts on the subject, 13 variables were considered relevant and classified according to their impact and dependency. Among the most influential variables were technological infrastructure, cross-sector collaboration, and environmental indicators, while available toxicological data and the regulatory framework were found to be the most dependent. The results reflect the need to strengthen cooperation among key institutional actors, promote technology, and continuously monitor to ensure the operation of early warning systems. This work contributes to the construction of a conceptual framework that contains the systemic dynamics that must be articulated in the design and implementation phases of early warning systems in complex contexts.